The Impact of Digitalization Through QRIS Utilization on MSMEs Performance in Expanding Market Reach and Enhancing Transaction Efficiency - Agustiani, Wulan; Anfas, Anfas (Peneliti.net, 2025)
The development of digital technology has had a profound impact on financial transaction systems and business patterns, particularly for Micro, Small, and Medium Enterprises (MSMEs). One of the most influential innovations is the Quick Response Code Indonesian Standard (QRIS), developed by Bank Indonesia. This study aims to analyze the effect of QRIS utilization on MSME actors in expanding market reach and enhancing transaction efficiency. The research employs a qualitative descriptive approach based on literature review and secondary data analysis obtained from Bank Indonesia, the Financial Services Authority (OJK), and the Ministry of Cooperatives and SMEs. The findings indicate that the adoption of QRIS has increased transaction efficiency by up to 35% and broadened the digital market reach of MSMEs. Nevertheless, several challenges persist, including low levels of digital literacy and limited network infrastructure in certain regions. This study affirms that QRIS plays a crucial role in strengthening financial inclusion and enhancing national economic competitiveness.